Experimental investigations and optimisation of process parameters in dry finish turning of Inconel 625 super alloy. (20th January 2020) - Hemakumar, S.; Kuppan, P.
This study presents an experimental investigation and optimisation of process parameters in dry finish turning of Inconel 625 nickel-based super alloy. The process parameters such as cutting speed and feed rate were varied for three levels keeping depth of cut constant at finish machining regime (0.5 mm). The experiments were conducted as per the full factorial design of experiments and the influence of process parameters on the output measures such as cutting force (Fc ), feed force (Ff ), average surface roughness (Ra ) and average flank wear (VB ), were analysed using ANOVA. Empirical models were developed for the output measures using response surface methodology and the regression analysis shows a good degree of fit. The optimal conditions for minimum Ra and VB were obtained through response optimisation composite desirability approach. Furthermore, the tool wear mechanism was studied and reported.